Efficient use of Ferrate(VI) in the remediation of aqueous solutions contaminated with potential micropollutants: Simultaneous removal of triclosan and amoxicillin (Indian Journal of Biochemistry and Biophysics (IJBB), 2023)
Ferrate(VI) is a safer oxidant compared to the often used oxidant in various wastewater treatment plants since the ferrate(VI) is devoid with the generation of harmful by-products. Hence, the present study is aimed to obtain laboratory experimental data for the treatment of water adulterated with emerging micro-pollutant (triclosan and amoxicillin) using the ferrate(VI). The parametric studies enabled us to deduce the kinetics of ferrate(VI) removal. The molar stoichiometry of ferrate(VI) and micro-pollutant was obtained as 2:1. Further, the mineralization of triclosan and amoxicillin is obtained which further enhances the applicability of ferrate(VI) in the waste water treatment. The simultaneous removal of these two pollutants (triclosan and amoxicillin) are extensively studied using the ferrate(VI). Moreover, the pH dependent degradation using ferrate(VI) is enabled to deduce the mechanism of removal. Additionally, the real matrix samples using the natural spring water (Tuikhur water) spiked with these micro-pollutants showed that the ferrate(VI) efficiency is almost unaffected at least in the removal of these two micro-pollutants. This showed the selectivity of the ferrate(VI) in the treatment process.